A Case-Control Study on the Therapeutic Effect of Mediastinoscope-Assisted and Thoracoscope-Assisted Esophagectomy. (June 2021) - Guo, Li; Zhao, Qian; Wang, Kairui; Zhao, Duowen; Ye, Xiaofeng; Li, Tao
Objective. To compare the clinical efficacies of mediastinoscope-assisted and thoracoscope-assisted esophagectomy. Materials and Methods. Seventy-six patients with esophageal cancer who underwent minimally invasive esophagectomy at the General Hospital of Ningxia Medical University between June 2015 and January 2019 were retrospectively evaluated. Among them, 28 patients underwent mediastinoscope-assisted transhiatal esophagectomy (MATHE), and 48 received thoracoscope-assisted transthoracic esophagectomy (TATTE). The perioperative clinical data and follow-up data of the 2 groups were compared. Results. All operations were successful in both groups. MATHE was favorable in terms of operation time, intraoperative blood loss, drainage volume 3 days after surgery, postoperative hospital stay, and hypoproteinemia ( P < .05). Lymph node dissections were less than those in the TATTE ( P < .05). No significant differences in long-term postoperative complications and survival rate were found between the 2 groups ( P > .05). Conclusion. MATHE has the advantages of minimal trauma, shorter operation time, less intraoperative blood loss, and faster recovery. More adequate tumor clearance in terms of lymph node dissection can be achieved with TATTE. However, the comparison of survival rates between the 2 groups is similar.